Character Strengths and Life Satisfaction of Slovenian In-service and Pre-service Teachers - Polona Gradišek (Center for Educational Policy Studies Journal)
Character strengths and life satisfaction of Slovenian in-service and preservice teachers were researched. The VIA-IS self-assessment questionnaire has been translated into the Slovenian language and has been used for the first time in Slovenia. A total of 173 primary school teachers and 77 student teachers from the Faculty of Education, University of Ljubljana, completed the VIA-IS and the Satisfaction with Life Scale questionnaires. The highest reported strengths in both groups studied were fairness, kindness, integrity and love. Unexpectedly, both in-service and pre-service teachers reported low endorsements of creativity; inservice teachers also showed low endorsement of humour. Surprisingly, the lowest endorsed strength of pre-service teachers was love of learning. Correlations between strengths and life satisfaction were consistent with related research findings. Low endorsement of creativity, teachers’ humour and students’ love of learning are discussed. From the research findings, it can be concluded that professional environment should stimulate, as well as provide support and opportunities for teachers to build not only upon the strengths of humanity and justice, but also on those of wisdom and knowledge. There is a need in the undergraduate level of teacher education for systematic interventions regarding students’ intellectual strengths with a special focus on cultivating their creativity.